Exploring tisotumab vedotin in recurrent cervical cancer: A case series including an HPV-independent gastric type adenocarcinoma - Lisa Marie Babayan; Catherine Bouts; Saketh Guntupalli; Nicole A. Marjon (Elsevier, 2024)
Metastatic and recurrent cervical cancer is difficult to treat with limited options following platinum-based chemotherapy. Tisotumab vedotin (TV) is an antibody drug conjugate (ADC) targeted at a tissue factor (TF), which is a cell surface protein that is upregulated in the majority of cervical cancers. Prior clinical trials have demonstrated efficacy of TV in metastatic and recurrent cervical cancer with an objective response rate of 24-26 % with an 8.3 month duration of response. In this case series, we present 3 patients with recurrent or progressive cervical cancer of three different histologies (squamous cell, adenocarcinoma, and human papillomavirus (HPV)-independent gastric type carcinomas). We demonstrate a 100 % complete response rate with average time of complete response of 4.33 months. The duration of response was not reached as none of our patients had a confirmed progression at the time of writing this manuscript, but the mean time since the initiation of treatment was 6.1 months. In concordance with the clinical trials, our patients tolerated TV well although the grade 3 ocular toxicities were higher in our patients compared to prior data. This case series presents data confirming the efficacy and tolerability of TV in patients with recurrent cervical cancer, including an HPV-independent gastric type cervical cancer.